RESIKO AUDIT LAPORAN KEUANGAN PADA SISTEM PENGENDALIAN INFORMASI AKUNTANSI: RESIKO AUDIT LAPORAN KEUANGAN PADA SISTEM PENGENDALIAN INFORMASI AKUNTANSI - ali topan lubis (JIBF MADINA : Journal Islamic Banking and Finance Madina, 2024)
Risk is an uncertainty in the future about losses. Risk is the obligation to bear losses caused by an event beyond the fault of one party. There are two aspects that need to be considered by financial management in making financial decisions, namely the rate of return and the risk of the financial decision. Determination of Accounting Information Control Risk Determination of control risk is the process of assessing the effectiveness of a company in preventing and detecting material misstatements in the preparation of financial statements. Control risk is determined for each transaction processing assertion, and because many control activities relate to specific types of transactions, auditors usually begin by determining risk for transaction group assertions such as existence or occurrence assertions, completeness, and valuation or allocation for cash receipts and cash disbursements transactions. Testing of control is a process used to ensure that a system or process is running in accordance with established standards and procedures. The purpose of testing of control is to ensure the quality, security, and efficiency of a system or process. Testing of control is a test carried out on the design of the implementation of a policy or procedure for the internal control structure.